Investments in Bonds, Stocks, Gold and Real Estate as a Hedge Against Inflation - Wolski, Rafal (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
In times of accelerating inflation, financial instruments that protect capital against loss of value are becoming increasingly important. Therefore, an open question remains as to what to invest in to, if not outstrip, at least keep up with the inflation rate in the case of return on investments. This raises the question of whether there are such opportunities in the market. However, according to some authors, this type of analysis is not easy and simple econometric methods are not able to show the appropriate dependencies. An example is real estate investment, which, especially in the short term, may not be a suitable inflation hedge. The purpose of the study is to determine whether investments in the Polish capital market are able to protect capital from depreciation due to inflation. The study began with the analysis of distributions, stationarity of returns and correlation of successive investments and the CPI inflation rate, ending with cointegration analysis using the Engle–Granger test. The analysis was performed from the first quarter of 2009 to the fourth quarter of 2021. The following indices were used for the study: the TBSPIndex from the bond market, the WIG from the stock market, gold prices in PLN, the NBP hedonic index of real estate prices in seven largest Polish cities and CPI inflation rates published by Statistics Poland (GUS). The analysis led to a negative verification of the research hypothesis, as it could not be proved that the analysed indices and prices are related to the level of inflation. The study fills a gap in the Polish market for analysis of capital protection against inflation. The research concerns only the Polish market, however this issue has not been discussed for years in mature economies either.